If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + 2x) + -5 = 25 (3 * 6 + 2x * 6) + -5 = 25 (18 + 12x) + -5 = 25 Reorder the terms: 18 + -5 + 12x = 25 Combine like terms: 18 + -5 = 13 13 + 12x = 25 Solving 13 + 12x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 12x = 25 + -13 Combine like terms: 13 + -13 = 0 0 + 12x = 25 + -13 12x = 25 + -13 Combine like terms: 25 + -13 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| 2-t=5+2t | | 17x^2-24xy=0 | | -1+3x=2x+11 | | 7-16-(-3-4)= | | -17+10-61-(-3)= | | 2(x+1)=2(x+3) | | (4x-1)^1/2=6 | | -16+10-61-(-3)= | | (5y+7)-(4+4y)=9 | | 3n^2-20n=-32 | | 10-5b=110 | | 2/3r=6 | | 8x+44=12x | | q/4+7=5 | | 2.4+(-3.7)= | | -3.8-2.9= | | -9-9-9-9= | | -60-(-8-3)= | | -9=-7+2y | | 12(12q+4)= | | 12-(1-5)= | | 45x+27y=1750 | | 26=4-u+2 | | 9-13-(-44)= | | -5(5x-7)+4=-25x+39 | | 36x^2-24x+4=0 | | h=3vt+19t^2 | | 9-13-(44)= | | 2(72+71b+7b^2)= | | 5x-8=3x-16 | | 4t+5+5t-8t=5+6 | | 4+7-20= |